ASSESSMENT OF MAIN LIPID METABOLISM INDICATORS IN PATIENTS WITH CHRONIC PANCREATITIS AND METABOLICALLY ASSOCIATED FATTY LIVER DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The prevalence of metabolic syndrome (MS), non-alcoholic fatty liver disease (NAFLD), and non-alcoholic fatty pancreatic disease (NAFPD) accounts for one-quarter to one-third of the world’s population. It has been proven that the key pathogenetic mechanisms of these conditions are disorders of lipid and carbohydrate metabolism. A high comorbidity between NAFLD and NAFPD has been demonstrated: 67.9% of patients with NAFPD were found to have hepatic steatosis, and 96.8% of patients with NAFLD were diagnosed with pancreatic steatosis.